2021
DOI: 10.3389/fenrg.2021.640664
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Investigation of Fullerene PC71BM and Non-fullerene ITIC-Th Acceptors Blended With P3HT or PBDB-T Donor Polymers for PV Applications

Abstract: Fundamentally, organic solar cells (OSCs) with a bulk-heterojunction active layer are made of at least two electronically dissimilar molecules, in which photoabsorption in one (donor) generates Frenkel excitons. The formation of free charge carriers emerge after exciton dissociation at the donor:acceptor interface. In the past decade, most of the progress in enhanced device performance has been steered by the rapid development of novel donor and acceptor materials and on device engineering. Among these donor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…The absorption spectra in each case are consistent with the device performance in terms of JV curves and IPCE measurements, which are higher in the WO 3 -slot-die and spray-coated samples compared to the WO 3 -spin-coated samples. Furthermore, each device has a strong absorption in the range of 500-700 nm, which is consistent with the complementary absorbance spectra between PBDB-T:ITIC [60,61], indicating that ITIC molecules exhibit strong and wide-ranging absorption properties, spanning from the visible spectrum to the near infrared, with their peak absorption occurring at 700 nm.…”
Section: Analysis Of Ipce Absorbance Spectra and Thickness Of Active ...supporting
confidence: 76%
“…The absorption spectra in each case are consistent with the device performance in terms of JV curves and IPCE measurements, which are higher in the WO 3 -slot-die and spray-coated samples compared to the WO 3 -spin-coated samples. Furthermore, each device has a strong absorption in the range of 500-700 nm, which is consistent with the complementary absorbance spectra between PBDB-T:ITIC [60,61], indicating that ITIC molecules exhibit strong and wide-ranging absorption properties, spanning from the visible spectrum to the near infrared, with their peak absorption occurring at 700 nm.…”
Section: Analysis Of Ipce Absorbance Spectra and Thickness Of Active ...supporting
confidence: 76%
“…The band found at 821 cm −1 corroborates the existence of aromatic C-H outside of simple vibrations and suggests that the structure of P3HT is composed of P3HTchains [ 36 ]. The peak at 1107 cm −1 is ascribed to the asymmetries of the C-O stretching bands [ 37 ]. The carbon-to-carbon single bond (C-C) is represented by the band at 1270 cm −1 [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The saturation photocurrent, J sat is determined from figure 4(a) and the maximum generation rate, G max is calculated from J sat = qG max L, where, q is the elementary charge and L is the thickness of the active layer [23]. G max is a measure of the maximum number of photons that can be absorbed by the active layer [24]. It can be observed that there is an enhancement in the J sat and G max values with increase of SQ content in the OSCs, suggesting an enhancement in light absorption.…”
Section: Resultsmentioning
confidence: 99%
“…The excitons generated by the absorption of the photons may not be fully dissociated into free carriers in the active layer. The exciton dissociation probability, P(E, T), provides a measure of how many photogenerated excitons would be dissociated into free charge carriers [24]. The exciton dissociation probability rate is determined to be only 81.5% for the binary device under short-circuit conditions, while it improves to about 94.9% when 25 wt.% SQ is introduced into the ternary OSCs, indicative of effective dissociation of excitons at the donor/acceptor interface and accounting for the improved J SC .…”
Section: Resultsmentioning
confidence: 99%